The Length of an Infarcted Lesion Along the Perforating Artery Predicts Neurological Deterioration in Single Subcortical Infarction Without Any Relevant Artery Stenosis - Jang, Seong Hwa; Park, Sang-Won; Kwon, Doo Hyuk; Park, Hyungjong; Sohn, Sung-Il; Hong, Jeongho (Frontiers in Neurology, 2020)
Objectives: The aim of our study was to assess image biomarkers of early neurological deterioration in single subcortical infarction (SSI) without any relevant artery stenosis. Methods: Between June 2005 and December 2009, consecutive patients with SSI within 24 hours of symptom onset were enrolled. Magnetic resonance angiography of the brain and neck was performed on all patients to confirm the absence of any stenosis of the relevant artery. Early neurological deterioration (END) was defined as neurological worsening by ≥ 2 points based on the initial National Institutes of Health Stroke Scale score during the first week after admission or prior to hospital discharge. A multiple logistic regression analysis was used to evaluate the independent predictors of END in SSI. Results: The final cohort consisted of 205 patients (109 males; 63.9 ± 11.0-years-old; ranging from 39 to 90), of whom 158 (77%) remained stable or improved and 47 (23%) showed neurological worsening. A univariate analysis revealed significant differences between patients with and without END in terms of maximum diameter of the largest area on an axial view and the number of slices showing the cerebral infarction on a transverse plane. A multiple logistic regression analysis revealed that the occurrence of three or more slices showing the cerebral infarction on a transverse plane was an independent predictor of END in SSI without relevant artery stenosis (1 vs 3; OR 14.281; 95% CI 1.76 ‒ 115.8; p = 0.013, 1 vs 4; OR 14.04; 95% CI 1.65 ‒ 119.57; p = 0.016) Conclusion: The longitudinal length of the infarcted lesion along the perforating artery predicts END in cases of acute SSI without any relevant artery stenosis.